2022
DOI: 10.1101/2022.03.11.22272269
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association of frailty, age, and biological sex with SARS-CoV-2 mRNA vaccine-induced immunity in older adults

Abstract: Background: Male sex and old age are risk factors for severe COVID-19, but the intersection of sex and aging on antibody responses to SARS-CoV-2 vaccines has not been characterized. Methods: Plasma samples were collected from older adults (75-98 years) before and after three doses of SARS-CoV-2 mRNA vaccination, and from younger adults (18-74 years) post-dose two, for comparison. Antibody binding to SARS-CoV-2 antigens (spike protein [S], S-receptor binding domain [S-RBD], and nucleocapsid [N]) and functional … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Their B and T cells are less responsive to outside stimuli. They are more likely to have a severe course of COVID-19 and are associated with higher mortality (Bubar et al, 2021;Ramasamy et al, 2021;Shapiro et al, 2022). Previous studies have also reported that patients aged >65 years had significantly lower serum antibody titers after vaccination (Ariamanesh et al, 2022;Erdogan et al, 2022).…”
Section: Discussionmentioning
confidence: 98%
“…Their B and T cells are less responsive to outside stimuli. They are more likely to have a severe course of COVID-19 and are associated with higher mortality (Bubar et al, 2021;Ramasamy et al, 2021;Shapiro et al, 2022). Previous studies have also reported that patients aged >65 years had significantly lower serum antibody titers after vaccination (Ariamanesh et al, 2022;Erdogan et al, 2022).…”
Section: Discussionmentioning
confidence: 98%
“…Age and male sex have been considered risk factors for COVID-19 disease [22][23][24][25][26]. While one might hypothesize that older individuals and/or males might have higher SARS-CoV-2 burdens and therefore lower Ct values at the time of testing, evidence for this is mixed, with some studies reporting lower Ct values in older individuals [24,27], others in younger individuals [28], and still others finding no difference by age [20,[29][30][31][32][33][34].…”
Section: Individuals Infected With Sars-cov-2 Despite Vaccination She...mentioning
confidence: 99%
“…Little is known about how sex may impact the immunogenicity and protection elicited by mRNA vaccine. Ageand frailty-associated decrease in humoral responses is greater in males than in females 49 . The age-related decreases in antibody titers observed in males have been also associated with a decline in CD4 + T cell responses 50 .…”
Section: Discussionmentioning
confidence: 90%